Melek Literasi Basis Budaya Sekolah di SD Berdasarkan Hasil Analisis Artikel - Jannah Mutiarani Pradana; Dinie Anggraeni Dewi; Rizky Saeful Hayat (Jurnal Multidisiplin Indonesia, 2023)
This article aims to examine the influence of school cultural base literacy in elementary schools in various different applications, so the author needs to examine several articles to find out the application of literacy in these schools. The research method used in this article is a qualitative approach with a literature study method. The method for reviewing journals was used by searching and collecting literature studies with the keyword "school cultural base literacy in elementary school". The author found 5 articles that could be studied according to the purpose of writing this article. The result of the study of the five articles is that the application of literacy in elementary schools based on school culture has been implemented as it should, only the difference between the five articles lies in their application. Some use traditional games, applications supported by the application of character education, and others are integrated with the Pancasila student profile.